2021
DOI: 10.1136/bmjdrc-2021-002123
|View full text |Cite
|
Sign up to set email alerts
|

Association between variability in body mass index and development of type 2 diabetes: Panasonic cohort study

Abstract: IntroductionContrasting results have been reported for the association between the variability in body weight and development of diabetes. In the present study, we evaluated the association between the variability in body mass index (BMI) and development of type 2 diabetes in 19 412 Japanese participants without obesity and without body weight gain or loss during the study period.Research design and methodsWe recorded body weight of the participants consecutively each year in Panasonic Corporation, Osaka, Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…Panasonic cohort study revealed that risk of developing type 2 diabetes mellitus increased 11.1% with 1% increase in coefficient of variation in BMI. 17 Our findings were consistent with these prior studies that higher BMI was associated with more co-morbidities such as hypertension and type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Panasonic cohort study revealed that risk of developing type 2 diabetes mellitus increased 11.1% with 1% increase in coefficient of variation in BMI. 17 Our findings were consistent with these prior studies that higher BMI was associated with more co-morbidities such as hypertension and type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 93%
“…They found out that when BMI increased 3 kg/m 2 , there is higher risk of hypertension by 65% in men and 83% in women compared to those with stable BMI. Panasonic cohort study revealed that risk of developing type 2 diabetes mellitus increased 11.1% with 1% increase in coefficient of variation in BMI 17 . Our findings were consistent with these prior studies that higher BMI was associated with more co‐morbidities such as hypertension and type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 92%
“…This study used the database of the Panasonic cohort study from 2008 to 2018. The Panasonic cohort study is described in detail elsewhere 14 . All participants received a blood examination every year.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…Several previous studies have examined the relationship between the consequence of variabilities in obesity measures on health outcomes in participants with or without diabetes but the results are inconsistent. Some studies have found variability in BMI to be associated with the development of diabetes [ 29 ], increased risk of new-onset atrial fibrillation and myocardial infarction [ 30 ], increased rate of hospitalization from heart failure [ 31 ], whiles WC variability has also been found to be associated with risk of stroke and all-cause mortality [ 28 ]. However, these studies did not assess the relationship between obesity variability and diabetic microvascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that a subsequent increase in weight after an initial decrease may be associated with a more rapid adipose tissue growth and hyperplasia due to metabolic shifts which favor lipid storage [ 15 ]. Since adipose tissue is a highly active metabolic endocrine organ [ 34 ], the rapid remodelling of adipose tissue linked to high obesity variability may provoke abnormal production of proinflammatory adipokines, which may potentially lead to adverse health outcomes including diabetes and its associated complications [ 15 , 17 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%